Does work have to be so painful? A review of the literature examining the effects of fibromyalgia on the working experience from the patient perspective - K. Mukhida; W. Carroll; R. Arseneault (Taylor & Francis Group, 2020)
Background Chronic pain conditions, such as fibromyalgia, adversely affect individuals' abilities to work. Aim The aim of this study was to examine, from the perspective of patients, the effects that fibromyalgia symptoms had on their ability to work, the challenges that they encountered in the workplace that did not foster their continued employment, and the types of modifications to their work or workplace that they thought would facilitate their productivity and ability to work. Methods A scoping review method, applying techniques of systematic review, was used to conduct a research synthesis of the literature regarding fibromyalgia and work that looked at this issue from the patient perspective. Results A variety of themes emerged from the analysis and could be broadly categorized into (1) the work experience was a challenging one with which to cope; (2) relationships were strained at work; (3) clinical symptoms had repercussions on subjects' attitudes toward work and the relation to life outside of work; and (4) a variety of possible solutions were considered to help subjects better cope with fibromyalgia and work. Conclusions Strategies that potentially could foster continued employment of patients with fibromyalgia include those at the micro, meso, and macro levels. Health care providers can support patients' employment goals by collaborating with patients and their employers, dispelling stigma regarding the illness, and providing practical and specific advice regarding workplace accommodations.